Numerical and Experimental Evaluation of Hydrodynamic Bearings Applied to a Jeffcott Test Bench - Cruchaga-Ssa., M (International Institute of Acoustics and Vibrations, 2021)
Merging analytical and numerical models with experimental results improve the behaviour predictions of mechanical elements applied to rotor machinery, such as the bearings. This work aims to present the design of a hydrodynamic bearing prototype, a comparison and validation between the numerical and experimental results of critical speeds, and the differences of behaviour when the bush geometries and lubrication are changed. The bush geometries and the fluid film properties are analysed by measuring the dynamic behaviour of a rotor supported by these bearings. The experimental evaluation is based on measuring the Jeffcott test bench supported in a pair of bearings, showing the anisotropic behaviour caused by the stiffness difference in horizontal and vertical directions. It also presents an optimization of bushings for isotropic conditions when they were changed for different geometries (elliptical, offset halves) and different materials with boundary lubrication. This detailed study shows how the dynamic behaviour of rotating machinery can be predicted using numerical models and its validation by a test rig. Results also show how the vibration occurs if the bushes geometries are modified or its lubrication condition is changed. © 2021 International Institute of Acoustics and Vibrations. All rights reserved.